A Proposed instructional material in reading readiness for pre-schoolers in the public elementary schools division of san pablo city - Pipit, Zerlene Mendoza (Manila : National University, 2001)
Ordinarily, before attending pre-schools, no child is ready on the physical, oral, auditory, visual and intellectual aspects. Failure to achieve reading readiness at a crucial period of development may result to inability to read with efficiency. This fact is based on the concept developed as the result of studies previously conducted regarding the nature of learning among children.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Table of contents -- List of tables -- List of figures -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, analysis, and interpretation of data -- Chapter 5. Summary, Conclusion, and recommendation -- Bibliography -- Appendices -- Reading Readiness Skills Exercises -- Curriculum Vitae.
Research Method : Descriptive Normative Research Method.
Includes bibliographical references.
Keywords: READING READINESS